THE LEADING TOURISM SECTOR RECOVERY STRATEGY AFTER THE COVID-19 PANDEMIC IN TANAH TORAJA - Sabandar, Sita Yubelina (Journal of Entrepreneur, Business and Management, 2024)
The COVID-19 pandemic has rocked economies around the world. The tourism sector is one of the sectors that the Coronavirus has battered. To avoid exposure to Covid-19, various tourist attractions ranging from museums, amusement parks, recreational parks, and various entertainment centers in Tanah Toraja, the leading destination in Indonesia, are entirely closed. One of the obstacles in the new average era is the behaviour of people who are still unsure and careful because they are afraid that the impact will increase the Covid-19 epidemic again. Facing this phenomenon, the Government of Tana Toraja needs to establish a strategy for recovery and significantly contribute to leading tourism. This qualitative research aims (1) to analyze the internal and external factors of Tana Toraja's leading tourism by mapping the demand and supply sides of leading tourist destinations. (2) analyzing the impact of the Covid-19 Pandemic on the Tourism Sector and (3) Formulating a leading tourism sector recovery strategy in Tana Toraja. This research is a case study in which the researcher investigates programs, events, processes, and activities of one or more people. Data collection in this study aims to obtain data related to research—the data collection method through the following stages: Interview, observation, and documentation. The stages of data analysis activities in this study can explain as follows. First, data reduction, secondly data presentation and third, conclusion. The results of this study provide input on strategies to strengthen the leading tourism sector to recover from the impact of the pandemic: (1) Mapping markets and tourists, (2) Mapping the demand side, (3) Mapping the supply side, (tourism industry/business sector), (4) Mapping competitiveness condition. (5) Identification of driving and inhibiting factors (6) Identification of the facilities needed to develop leading tourist destinations that comply with national and international standards